PREŠEREN IN KOSESKI – PRIMERJAVA KANONIČNEGA POLOŽAJA IN RECEPCIJSKE ZAHTEVNOSTI NJUNE POEZIJE (Filološke pripombe, 2019)
Jovan V. Koseski and France Prešeren were poets to whom literary history attributes undisputed merits for the development of Slovenian national conscience - to the former in the mid 19th century, and to the latter from the 1860s to today. The difference is mainly in the view of the artistic value of their poetry, as Slovenian literary history attributes to Prešeren the status of a top-level European poet, while it denies any significant aesthetic dimensions of the poetry of Koseski. An empirical study among Slovenian secondary school students showed that Prešeren's poems are more difficult to understand than Koseski's poems, mainly due to the many abstract metaphors. Namely, almost half of the surveyed participants attributed greater artistic value to XVI. glosa by Koseski than to Prešeren's Glosa.
Keywords: Prešeren, Koseski, canon, reception, empirical study